Pengembangan Modul Pembelajaran Berbasis Kearifan Lokal Suku Sasak pada Mata Pelajaran IPAS Materi Bab 6 Indonesiaku Kaya Budaya Kelas IV SDN Bejelo - Aulia Hasibatun Abkariah; Khairun Nisa; Muhammad Tahir (Mataram University, 2026)
This study was motivated by the use of general teaching materials that have not integrated Sasak local wisdom into IPAS learning, despite the Merdeka Curriculum's emphasis on contextual learning.This study aims to determine the development process, feasibility, and practicality of a learning module based on Sasak local wisdom in the IPAS subject, Chapter 6 “My Indonesia is Rich in Culture,” Topic A: The Uniqueness of Community Customs around Me for Grade IV students at SDN Bejelo. This research is Research and Development (R&D) using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects were fourth-grade students at SDN Bejelo. Data were collected through questionnaires and documentation. Research instruments included validation sheets from media and material experts, as well as response questionnaires from teachers and students. The results indicate that the module is feasible and practical. Material expert validation obtained a score of 56 (93%) categorized as “Highly Feasible,” while media expert validation obtained 40 (80%) categorized as “Feasible.” The module was also considered practical based on user responses. The small group trial reached 87% and the large group trial reached 95%, both categorized as “Highly Practical.” The teacher response obtained 86%, also categorized as “Highly Practical.” Based on these results, the Sasak local wisdom-based learning module is feasible and practical for Grade IV IPAS learning in elementary school.